Extremely low N2O concentrations in the springtime stratosphere at McMurdo Station, Antarctica - Parrish, A.; De Zafra, R. L.; Jaramillo, M.; Connor, B.; Solomon, P. M. (1988)
Measurements have been made of stratospheric N2O using the Stony Brook millimeter-wave remote sensing spectrometer at McMurdo Station, and NO2 mixing ratios are found that are less than 1.5 at 20 km and less than 1.10 at 25 km compared to values measured during the Antarctic summer. The observed mixing ratios are also much less than those predicted by global-scale models of stratospheric chemistry and dynamics. As the NO2 signal remained very weak when McMurdo was at the edges of the ozone hole and showed no signs of recovering during October, it is concluded that the geographical and temporal extent of the region of low NO2 is comparable to or greater than that of the ozone hole. These results argue against theories that require springtime upwelling to explain the Antarctic ozone hole. It is suggested that the air in the Antarctic lower stratosphere during late winter and early spring has been subjected to considerable downward transport.